Los macronutrientes nitrógeno, fósforo y potasio, en la producción del cultivo de papaya (Carica papaya L.) en Ecuador. - Ibarra Lara, María de los Ángeles (2023)
The objective of this document was to establish the importance of the macronutrients nitrogen, phosphorus and potassium in the production of papaya crops in Ecuador. Its development was based on the collection of information from virtual libraries, updated texts, magazines and articles, papers, congresses and any scientific bibliographic material. The information collected was subjected to processes of analysis, synthesis and summary. In the cultivation of papaya, nitrogen (N) is essential for the utilization of carbohydrates, to stimulate the development and growth of the plant; phosphorus (P) has a more important effect on photosynthesis, flowering, fruiting, seed formation, fruit ripening and root development; potassium (K) acts as an activator of enzymes responsible for starch synthesis, nitrate reduction and sugar degradation, as well as increasing the resistance of the crop against diseases and, in relation to production, increasing the number of fruits. Nitrogen is responsible for the growth of papaya plants and the green coloration of leaves, it is a constituent of amino acids, being crucial for protein synthesis. The macronutrients most consumed by the papaya crop are nitrogen and potassium, and to a lesser extent phosphorus, all of which are important for development, growth and production. The extraction of nutrients by the aerial organs of the papaya crop are nitrogen (140 kg/ha), phosphorus (13.5 kg/ha) and potassium (145 kg/ha). Applications of 290 kg of nitrogen, 219 kg of P20 and 129 kg of K20 Ha-1 should be made to achieve an adequate yield in the papaya crop.